The Effectiveness of Centrifugal Pump Shaft Alignment Process Against Vibration Reduction - Mulyadi, Rahmad; Darto, Darto; Iswantoko, Agus (Universitas Merdeka Malang, 2022)
Centrifugal pump is one of the most important components that is widely used by industry and functions to move liquids in the form of water or other liquid. One of the things that often happens on centrifugal pumps is the occurrence of high vibrations and abnormal sounds. High vibration in the pump is something that should be anticipated because it can cause damage to the bearings, seals, and shafts. If the pump continues to operate in this condition, it will also cause damage to other pump components and cause the pump to stop operating. Therefore, the condition of the pump must be monitored regularly to ensure that the pump can operate properly. One of the most frequently used methods to find out where high vibrations come from is to use the aptitude analyst application that will produce a unique vibrational spectrum. Vibration analysis is done by observing the amplitude and frequency of the vibration signal. Vibration spectrum analysis can detect pump damage without having to disassemble the equipment and can provide early warning before major damage occurs and takes a large repair cost. The results showed that the existence of high vibration at the 11-PA-7131A pump was caused by the parallel misalignment that occurred at the pump shaft and motor. This is indicated by the high amplitude of vibration on orders 1x, 2x and followed by the presence of amplitude on orders 3x. Vibration data retrieval after the alignment process on the pump shaft and motor also proves that there is a very significant change in vibration amplitude on orders 1x, 2x, and on order 3x. Overall vibration also experienced a very significant decrease so that the pump can be operated normally.